Integrasi Peran Guru dan Orang Tua dalam Meningkatkan Kualitas Pembelajaran Anak Sekolah Dasar (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
This study aims to examine the role of teachers and parents in supporting the learning process of elementary school children today through a literature review method. The study reviews seven national and international journals published between 2019 and 2024. The review results show that parental involvement and the role of teachers together have a significant positive impact on students’ academic achievement and socio-emotional development. However, there is a research gap regarding the simultaneous integration of teacher and parent roles, especially in the context of online learning. The practical implications of this study emphasize the importance of active collaboration between teachers and parents to improve the effectiveness of learning at the elementary level. This research is expected to contribute to the development of adaptive and responsive educational strategies to meet the needs of elementary school children in the digital era.